Вплив глобалізації на структуру соціальноекономічних потреб людини - Мурашова, Анна Олегівна; Murashova, A.O. (Харків : Харківській національний університет імені В. Н. Каразіна, 2019)
Запропоновано новий поведінковий аспект методології дослідження, поєднання якого з відтворювальним і соціально-структурним дозволяє більш комплексно охарактеризувати структурні зміни об'єкта дослідження. В роботі характеризована фундаментальна асиметрія в структурі людських потреб, що посилюється в умовах глобалізації, та в умовах безмежного зростання потреб стає джерелом поглиблення екологічних, антропологічних та інших глобальних криз. Виділено основні тенденції впливу глобалізації на зміни структури потреб людини: стандартизація, індивідуалізація, інформатизація, віртуалізація. Показано, що оптимізація структури соціально-економічних потреб здійснюється шляхом їх гуманізації та соціалізації.

The thesis presents the systematic and conceptual research of theoretical and methodological basis of transforming social and economic needs of people as subjects of market relationships. Due to the changes in the structure of social and economic needs under the conditions of globalization there have been outlined the methodological approaches as for their research and these changes have been thoroughly studied. The combination of theoretical provisions of the main existing approaches – reflective and behavioral – in studying social and economic needs enabled to interpret their content as a complex interdisciplinary issue. It is emphasized that in the modern conditions the most influential factor of interpreting institutional presupposition and the subjective character of the system of changes is presented by globalization context.
Impact of Globalization on the Structure of Social and Economic Human Needs
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; соціально-економічні потреби; закон піднесення потреб; глобалізація; стандартизація та індивідуалізація потреб; суспільство споживання; перетворені і вільні форми потреб; гуманізація і соціалізація потреб; social and economic needs; law of needs’ enhancement; globalization; standardization and individualization of needs; consumer society; transformed and free forms of needs; humanization and socialization of needs